Prognostic significance of annexin A2 and annexin A4 expression in patients with cervical cancer. Issue 1 (December 2016) - Choi, Chel; Chung, Joon-Yong; Chung, Eun; Sears, John; Lee, Jeong-Won; Bae, Duk-Soo; Hewitt, Stephen
Abstract Background The annexins (ANXs) have diverse roles in tumor development and progression, however, their clinical significance in cervical cancer has not been elucidated. The present study was to investigate the clinical significance of annexin A2 (ANXA2) and annexin A4 (ANXA4) expression in cervical cancer. Methods ANXA2 and ANXA4 immunohistochemical staining were performed on a cervical cancer tissue microarray consisting of 46 normal cervical epithelium samples and 336 cervical cancer cases and compared the data with clinicopathological variables, including the survival of cervical cancer patients. Results ANXA2 expression was lower in cancer tissue (p =  0.002), whereas ANXA4 staining increased significantly in cancer tissues (p <  0.001). ANXA2 expression was more prominent in squamous cell carcinoma (p  < 0.001), whereas ANXA4 was more highly expressed in adeno/adenosquamous carcinoma (p  < 0.001). ANXA2 overexpression was positively correlated with advanced cancer phenotypes, whereas ANXA4 expression was associated with resistance to radiation with or without chemotherapy (p =  0.029). Notably, high ANXA2 and ANXA4 expression was significantly associated with shorter disease-free survival (p  = 0.004 andp  = 0.033, respectively). Multivariate analysis indicated that ANXA2+ (HR = 2.72, p  = 0.003) and ANXA2+/ANXA4+ (HR = 2.69, p  = 0.039) are independent prognostic factors of disease-free survival in cervical cancer. Furthermore, a random survival forest model using combined ANXA2, ANXA4, and clinical variables resulted in improved predictive power (mean C-index, 0.76) compared to that of clinical-variable-only models (mean C-index, 0.70) (p  = 0.006). Conclusions These findings indicate that detecting ANXA2 and ANXA4 expression may aid the evaluation of cervical carcinoma prognosis.